2014
DOI: 10.3855/jidc.4179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the novel IMP-38 among carbapenemase-producing Enterobacteriaceae in a university hospital, China

Abstract: Introduction: This study set out to investigate the molecular epidemiology of carbapenemase-producing Enterobacteriaceae isolates collected from Xiang Ya Hospital, Hunan, China. Methodology: The carbapenemase genes from Enterobacteriaceae isolates were determined by PCR and sequencing. Relatedness of Klebsiella pneumoniae isolates was evaluated by pulsed-field gel electrophoresis. Results: Twenty-four out of 738 non-repetitive Enterobacteriaceae isolates harbored carbapenemase genes including IMP-38, a novel I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…1). Similar results have also been reported in other studies from China [9, 13, 14, 16, 20]. These studies showed that the effects of IMP hydrolase on different carbapenems may be diverse, and therefore, the carbapenem-sensitive phenotype does not mean negative for carbapenemase.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1). Similar results have also been reported in other studies from China [9, 13, 14, 16, 20]. These studies showed that the effects of IMP hydrolase on different carbapenems may be diverse, and therefore, the carbapenem-sensitive phenotype does not mean negative for carbapenemase.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, IMPKpn exhibited sporadic prevalence in our hospital. In China, IMPKpn isolates have been identified across the country, and the main variants are IMP-4 and IMP-8 [3, 6, 7, 921], while IMP-26 and IMP-38 have also been identified [16, 18]. In this study, besides the scattered emergence of IMP-1, IMP-26 and IMP-38, we found that the majority of IMPKpn isolates produced IPM-4 (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…reported that strains producing the IMP-type carbapenemase were the main cause for the carbapenem resistance in K. pneumoniae in our hospital. [11] However, in our previous studies, CR-KP isolates collected during the outbreak were all shown to produce KPC and to be resistant to all antimicrobial agents tested except for colistin and cotrimoxazole. Thus, these isolates were found to be extensively drug-resistant strains with limited treatment options for infections due to these strains.…”
Section: Introductionmentioning
confidence: 94%
“…The yearly frequencies of IMP-38-producing K. pneumoniae clinical isolates were 2.04% (1/49) in 2013, 0.0% (0/82) in 2014, 2.72% (2/88) in 2015, and 3.77% (11/296) in 2016. The results suggested that the IMP-38-producing isolates had persisted in our hospital since the initial identification (12).…”
Section: Resultsmentioning
confidence: 82%
“…IMP carbapenemase, a member of the metallo-␤-lactamases capable of hydrolyzing almost all ␤-lactams, was first described in Japan in the 1990s (11). In 2011, our group first identified a novel IMP-38 variant in the neonatology department in our hospital (12). In this study, we examined the prevalence of bla IMP-38 -harboirng K. pneumoniae isolates in our hospital and determined their genetic backgrounds.…”
mentioning
confidence: 98%